Pathophysiology of hepatic encephalopathy and future treatment options - J.A. González-Regueiro; M.F. Higuera-de la Tijera; R. Moreno-Alcántar; A. Torre (Revista de Gastroenterología de México (English Edition), 2019)
Understanding of the pathophysiology of hepatic encephalopathy has conditioned new treatment options. Ammonia detoxification in hepatic encephalopathy is regulated by two enzymes: glutaminase or glutamine synthetase. The first produces ammonia and the second detoxifies the ammonia, which is why treatments are aimed at glutaminase inhibition or glutamine synthetase activation. At present, we know that both enzymes are found not only in the liver, but also in the muscle, intestine, kidney, and brain. Therefore, current treatments can be directed at each enzyme at different sites. Awareness of those potential treatment sites makes different options of approach possible in the patient with hepatic encephalopathy, and each approach should be personalized. Resumen: El entendimiento de la fisiopatología de la encefalopatía hepática ha condicionado nuevas opciones de tratamiento. La detoxificación del amonio es regulada por 2 enzimas en la encefalopatía hepática: la glutaminasa o la glutamina sintetasa. La primera genera amonio y la segunda detoxifica el amonio, por lo que los tratamientos son encaminados a la inhibición de la glutaminasa o a la activación de la glutamina sintetasa. Actualmente sabemos que ambas enzimas se encuentran no solo en el hígado, sino también en el músculo, intestino, riñón y cerebro, por lo que los tratamientos actuales pueden ser dirigidos a cada enzima en sitios separados. Entendiendo estos sitios potenciales de tratamiento, las opciones para el abordaje del paciente con encefalopatía hepática son diversas y deben ser personalizadas. Keywords: Encephalopathy, Intestine, Muscle, Astrocyte, Kidney, Detoxification, Palabras clave: Encefalopatía, Intestino, Músculo, Astrocito, Riñón, Detoxificación